DEVELOPING LEARNERS’ READING SKILLS IN SECONDARY EDUCATION (Conferencea, 2022)
In this article, reading is reflected as a prominent skill in second language acquisition. Also, some effective approaches, techniques and ways of developing learners’ reading comprehension are suggested.